Juncture prosody across languages: Similar production but dissimilar perception - Ip, Martin Ho Kwan; Cutler, Anne (Laboratory phonology, 2022)
How do speakers of languages with different intonation systems produce and perceive prosodic junctures in sentences with identical structural ambiguity? Native speakers of English and of Mandarin produced potentially ambiguous sentences with a prosodic juncture either earlier in the utterance (e.g., “He gave her # dog biscuits,” “他给她#狗饼干 ”), or later (e.g., “He gave her dog # biscuits,” “他给她狗 #饼干 ”). These productiondata showed that prosodic disambiguation is realised very similarly in the two languages, despite some differences in the degree to which individual juncture cues (e.g., pausing) were favoured. In perception experiments with a new disambiguation task, requiring speeded responses to select the correct meaning for structurally ambiguous sentences, language differences in disambiguation response time appeared: Mandarin speakers correctly disambiguated sentences with earlier juncture faster than those with later juncture, while English speakers showed the reverse. Mandarin-speakers with L2 English did not show their native-language response time pattern when they heard the English ambiguous sentences. Thus even with identical structural ambiguity and identically cued production, prosodic juncture perception across languages can differ.